A methodology for integrating web based FMEA and TRIZ - Awad, Ammar Ali (2014)
Failure Mode and Effect Analysis (FMEA) is a problem prevention technique predominantly used in industry. The applications of FMEA in Malaysia’s automotive manufacturing firms are currently manually done on hard copies or into spreadsheets. However, these conventional approaches are not highly effective, since they are not living documents, and they involve tedious data maintenance and updating. Above that, the recommended actions are usually taken based on the accumulation of experience based on personal memory. This research aims to convert a traditional process FMEA approach into an open architecture Process FMEA Web–based system, in conjunction with the automotive standard control plans, and to integrate invention problem solving methods (TRIZ) with this Web-based system. The Web-Based PFMEA model was validated using PFMEA data and failure reports provided by the Malaysian automotive manufacturing. This approach will help the process engineer to take action proactively when updating PFMEA and to improve or modify process control plans at a much lower cost. Integrated TRIZ with Web-based PFMEA can further assist in solving problems quickly and effectively. It also support engineers to look for the most highly effective and creative solutions.